An SMC ATPase mutant disrupts chromosome segregation in Caulobacter - Schwartz, Monica A. (2011)
Accurate replication and segregation of the bacterial genome are essential for cell cycle progression. We have identified a single amino acid substitution in the Caulobacter Structural Maintenance of Chromosomes (SMC) protein that disrupts chromosome segregation and cell division. The E1076Q point mutation in the SMC ATPase domain caused a dominant-negative phenotype in which DNA replication was able to proceed, but duplicated parS centromeres, normally found at opposite cell poles, remained at one pole. The cellular positions of other chromosomal loci were in the wild-type order relative to the parS centromere, but chromosomes remained unsegregated and appeared to be stacked upon one another. Purified SMC-E1076Q was deficient in ATP hydrolysis and exhibited abnormally stable binding to DNA. We propose that SMC spuriously links the duplicated chromosome immediately after passage of the replication fork. In wild type cells, ATP hydrolysis opens the SMC dimer, freeing one chromosome to segregate to the opposite pole. The loss of ATP hydrolysis causes the SMC-E1076Q dimer to remain bound to both chromosomes, inhibiting segregation.